2023
DOI: 10.1002/sstr.202300264
|View full text |Cite
|
Sign up to set email alerts
|

Size‐ and Temperature‐Dependent Lattice Anisotropy and Structural Distortion in CsPbBr3 Quantum Dots by Reciprocal Space X‐ray Total Scattering Analysis

Federica Bertolotti,
Nicola Dengo,
Antonio Cervellino
et al.

Abstract: Lead halide perovskite nanocrystals (NCs) have emerged as next‐generation semiconductors capable of unifying superior photoemission properties, facile and inexpensive preparation, compositional and structural versatility. Among them, CsPbBr3 is a model system in theoretical and experimental studies owing to its intrinsic chemical stability. Nonetheless, knowledge of the precise magnitude and the size‐ and temperature‐dependent lattice and structural distortions is lacking, and the static/dynamic nature of diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
1
0
0
Order By: Relevance
“…Similar fit parameters are also obtained for the TEM dataset, albeit with a slightly higher estimate for the bulk band gap. Overall, we conclude that the electron and hole effective masses, dielectric constant, and, thus, the exciton Bohr diameter should be comparable in AZPbBr 3 and CsPbBr 3 (see also Tables S4–S6), , while the bulk band gap of AZPbBr 3 appears few tens of millielectronvolts lower than in CsPbBr 3 ( E 0 = 2.38 eV in CsPbBr 3 ) . We also note that a previous estimate for the bulk AZPbBr 3 band gap by Petrosova et al found an even lower value (2.27 eV); however, their different definition for the band gap (via the zero-crossing in a Tauc plot) precludes a direct comparison to the values found by us for AZPbBr 3 and by Mannino et al for CsPbBr 3 (in both cases defined via second derivatives).…”
Section: Resultssupporting
confidence: 69%
“…Similar fit parameters are also obtained for the TEM dataset, albeit with a slightly higher estimate for the bulk band gap. Overall, we conclude that the electron and hole effective masses, dielectric constant, and, thus, the exciton Bohr diameter should be comparable in AZPbBr 3 and CsPbBr 3 (see also Tables S4–S6), , while the bulk band gap of AZPbBr 3 appears few tens of millielectronvolts lower than in CsPbBr 3 ( E 0 = 2.38 eV in CsPbBr 3 ) . We also note that a previous estimate for the bulk AZPbBr 3 band gap by Petrosova et al found an even lower value (2.27 eV); however, their different definition for the band gap (via the zero-crossing in a Tauc plot) precludes a direct comparison to the values found by us for AZPbBr 3 and by Mannino et al for CsPbBr 3 (in both cases defined via second derivatives).…”
Section: Resultssupporting
confidence: 69%